2023
DOI: 10.3390/ijms24076777
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Research on the Physiology and Molecular Regulation of Sorghum Growth under Salt Stress by Gibberellin

Abstract: Plant growth often encounters diverse abiotic stresses. As a global resource-based ecological problem, salinity is widely distributed and one of the major abiotic stresses affecting crop yields worldwide. Sorghum, a cereal crop with medium salt tolerance and great value for the development and utilization of salted soils, is an important source of food, brewing, energy, and forage production. However, in soils with high salt concentrations, sorghum experiences low emergence and suppressed metabolism. It has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 138 publications
1
17
0
Order By: Relevance
“…Excessive salt interferes with normal biological and physiological processes to negatively impact plant growth ( Talubaghi et al, 2022 ), such as reduced plant height, narrowed stem base width, and diminished biomass. The results obtained from the experimentation performed in this study were similar to those reported previously ( Ashraf et al, 2023 ; Liu et al, 2023 ; Feng et al, 2021 ; Talubaghi et al, 2022 ). More specifically, under salt stress, the seedling growth of both HHZ and XLY900 was significantly inhibited, and all the morphological indexes were decreased ( Tables 1 and 2 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Excessive salt interferes with normal biological and physiological processes to negatively impact plant growth ( Talubaghi et al, 2022 ), such as reduced plant height, narrowed stem base width, and diminished biomass. The results obtained from the experimentation performed in this study were similar to those reported previously ( Ashraf et al, 2023 ; Liu et al, 2023 ; Feng et al, 2021 ; Talubaghi et al, 2022 ). More specifically, under salt stress, the seedling growth of both HHZ and XLY900 was significantly inhibited, and all the morphological indexes were decreased ( Tables 1 and 2 ).…”
Section: Discussionsupporting
confidence: 91%
“…Globally, salt stress is the most prevalent abiotic stress that limits crop growth and development. Studies have shown that salt stress impedes the growth of several crops, such as wheat ( Ashraf et al, 2023 ), sorghum ( Liu et al, 2023 ), and soybean ( Feng et al, 2021 ). Excessive salt interferes with normal biological and physiological processes to negatively impact plant growth ( Talubaghi et al, 2022 ), such as reduced plant height, narrowed stem base width, and diminished biomass.…”
Section: Discussionmentioning
confidence: 99%
“…NaCl stress inhibits plant growth, reduces plant leaf area, decreases plant biomass, and may even lead to plant death. Inhibition of crop growth by NaCl stress has been reported in a variety of crops, such as rice [ 49 , 50 ], wheat [ 51 ], and sweet sorghum [ 52 ]. Nitrogen (N), an important component of plant protein, has an essential role in rice cultivation [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Talaye), the exogenous application of MeJA increased the soluble sugar level, relative water content, and photosynthetic rate to counteract the inhibitory effect of NaCl [ 54 ]. In sorghum, the exogenous application of gibberellins (GAs) can alleviate salt-stress-induced cell wall thickening by increasing the cellulose and hemicellulose content of root cells, allowing the rapid entry of water into root cells, and altering the dynamic balance of endogenous hormones in cells, thereby mitigating the effects of salt stress on germination and seedling growth [ 55 ]. Under high-salt conditions, ABA can stimulate short-term responses such as stomatal closure, thereby maintaining the water balance and mediating long-term growth responses by regulating the expression of stress-response genes [ 56 ].…”
Section: Discussionmentioning
confidence: 99%